﻿Revision of the endemic African genus Dinapsis (Dinapsini, Megalyridae, Hymenoptera) with description of seven new species - Simon van Noort; Scott Richard Shaw; Robert S. Copeland (ZooKeys, 2022)
The endemic Afrotropical genus Dinapsis is revised, and seven new species are described and illustrated: D. bicolor van Noort & Shaw, sp. nov., D. gamka van Noort & Shaw, sp. nov., D. igneus van Noort & Shaw, sp. nov., D. spinitibia van Noort & Shaw, sp. nov., D. taita van Noort & Shaw, sp. nov., D. tricolor Shaw & van Noort, sp. nov., D. zulu Shaw & van Noort, sp. nov. The distribution of the Central African Republican species D. centralis Shaw & van Noort, 2009 is extended to include Cameroon, Kenya and Uganda. Dinapsis turneri Waterston, 1922, previously only known from the poorly preserved holotype female, is redescribed based on newly collected specimens. The distribution of this Western Cape species is extended to include the Eastern and Northern Cape provinces of South Africa. Four distinct species groups within the genus are proposed and diagnosed. An illustrated identification key to all described species of Dinapsis is provided. Online interactive Lucid keys to Afrotropical megalyrid genera and Dinapsis species are available at http://www.waspweb.org.